Determining a theoretical and an empirical-based interactive multimedia Arabic language courseware to teach Arabic as a foreign language: Malaysian experience - Faryadi, Qais; Abu Bakar, Zainab; Maidinsah, Hamidah (2008)
The problem investigated in this research was that the majority of foreign language classes are taught with little or no regard for the current field-tested paradigm of foreign language acquisition.Many teachers are using almost an outdated paradigm of teaching in the classrooms.The prime objective of this experimental research was to compare the effect of two different instructional design interventions in teaching Arabic as a foreign language to 3rd grade students of Sekolah Taman Setiawangsa Kuala Lumpur Malaysia with a total of 82 students.In the process this research has developed an effective interactive field-tested Arabic Language Courseware called (BAIK) (Bahasa Arab Interaktif Kurikulum) as an alternative paradigm to the traditional learning in Malaysian classrooms.In this research the researcher applied a mixed method approach of quantitative and qualitative design in carrying out the investigation.The independent variables in this research are the methods of instructions(BAIK & traditional methods) while the dependant variables are learners’ comprehension, satisfaction, motivation, critical thinking and students’ final grade achievements. Instruments used to collect data were Pre-test, Post-test, interviews and questionnaires.Results showed that BAIK statistically improved students’ performance in the final exam compared to the traditional method.Results also suggested that BAIK improved learners’ attitudes, satisfaction, motivation and perception about learning the Arabic as a foreign language in classroom.